Rekrutmen partai politik dalam pencalonan Pemilu anggota DPRD Kabupaten Simalungun tahun 2019 - Novembri Yusuf Simanjuntak (Universitas Airlangga, 2022)
This study examines the lack of preparedness of political parties as electoral participants in proposing their cadres to become candidates for DPRD members in Simalungun District in 2019 elections. The purpose of this study is to describe and explain the conditions that resulted in the lack of preparedness of political parties in nominating DPRD members. The data collection process is carried out by analyzing the nomination documents given by political parties, especially documents that do not meet the requirements, and interviews with liaison officers or members of political party screening. The data obtained were analyzed using qualitative methods. The results of the study indicate that the number of candidates who do not meet the requirements because they do not complete the nomination requirements file, prove the lack of preparedness and failure of political parties to carry out the regeneration and recruitment functions. Cadreization and democratic recruitment functions are absolutely necessary so that candidates appear ready to compete to win the people's votes in the 2019 legislative elections.